An Evaluation of the Quality Educational Services in D3 Computerized Accounting at Politeknik Negeri Banjarmasin with the Matrix Method Importance Performance Analysis - Priyougie, Priyougie; Haq, Ahsanul; Rusniati, Rusniati (PPSDP International Journal of Education, 2024)
Evaluation of the quality of educational services is an important process to assess the extent to which an educational institution is able to meet the needs of students and provide quality services. Therefore, there is a need for consistent evaluation of continuous improvements to the quality of educational services to achieve customer needs and satisfaction, especially for the D3 Computerized Accounting Study Program, Accounting Department, Politeknik Negeri Banjarmasin (POLIBAN). By improving the satisfaction of all stakeholders involved in academic services, it is hoped that it can increase the number of prospective new students and the competitiveness of graduates so that they can be accepted into the D3 Computerized Accounting Study Program, Accounting Department, POLIBAN. This research aims to evaluate the quality of educational services in the D3 Computerized Accounting Study Program, Accounting Department, POLIBAN using the Importance Performance Analysis Matrix method. The research results found that there was a significant difference between expectations and perceptions regarding educational services in the D3 Computerized Accounting Study Program, Accounting Department, POLIBAN. This research provides recommendations to the D3 Computerized Accounting Study Program, Accounting Department, POLIBAN, to make continuous improvements so as to increase the number of students entering the D3 Computerized Accounting Study Program, Accounting Department, POLIBAN.